2014
DOI: 10.1007/s10616-014-9750-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of agitation speed in spinner flask for microcarrier structural integrity and expansion of induced pluripotent stem cells

Abstract: In recent times, the study and use of induced pluripotent stem cells (iPSC) have become important in order to avoid the ethical issues surrounding the use of embryonic stem cells. Therapeutic, industrial and research based use of iPSC requires large quantities of cells generated in vitro. Mammalian cells, including pluripotent stem cells, have been expanded using 3D culture, however current limitations have not been overcome to allow a uniform, optimized platform for dynamic culture of pluripotent stem cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…The characterization of commercial bioreactors has not been conducted until recent years [32][33][34]; furthermore, only limited mechanical parameters at a few speeds were investigated in these studies. Recently, Gupta et al [35] showed that the high rotational speeds could damage the microcarriers. The study also highlighted the optimum rotational speed corresponds to the highest mouse induced pluripotent cell yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of commercial bioreactors has not been conducted until recent years [32][33][34]; furthermore, only limited mechanical parameters at a few speeds were investigated in these studies. Recently, Gupta et al [35] showed that the high rotational speeds could damage the microcarriers. The study also highlighted the optimum rotational speed corresponds to the highest mouse induced pluripotent cell yield.…”
Section: Introductionmentioning
confidence: 99%
“…The study also highlighted the optimum rotational speed corresponds to the highest mouse induced pluripotent cell yield. Understanding the flow properties associated to the culture condition would enable researchers to gain advantage in optimising the culture process [35].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum concentration of MCs has not been reported, as it is dependent on cell type, MC properties, bioreactor type, and culture volume. However, a diverse range of ≈3000 MCs mL −1 to ≈15 000 MCs mL −1 is reported in the literature …”
Section: Concentration And/or Filtrationmentioning
confidence: 99%
“…More vigorous stirring and aeration are required to maintain the mass transfer rate of nutrients and gases for larger number of cells (Xing et al, 2009). However, this increases hydrodynamic shear stress, which produces adverse effects on cells, such as reduced proliferation, low viability, and uncontrolled differentiation of stem cells (Croughan, Hamel, & Wang, 1987;Gupta et al, 2016;Leung, Chen, Choo, Reuveny, & Oh, 2010;Ng, Berry, & Butler, 1996;O'Connor & Papoutsakis, 1992). The trade-off between the mass transfer rate and the hydrodynamic shear stress makes largescale expansion of shear-sensitive cells unreliable and leads to timeconsuming optimization of operating conditions on each expansion stage, as those factors are typically affected by the bioreactor's capacity.…”
mentioning
confidence: 99%